2006
DOI: 10.1136/jnnp.2005.065755
|View full text |Cite
|
Sign up to set email alerts
|

Raised CSF phospho-tau concentrations in variant Creutzfeldt-Jakob disease: diagnostic and pathological implications

Abstract: Objective: To investigate whether phosphorylated tau protein (tau-pT181) is increased in variant Creutzfeldt-Jakob disease (vCJD) and if the tau-pT181/tau protein ratio is useful for distinguishing between patients with and without CJD. Methods: CSF tau protein and tau-pT181 were measured in 50 patients with sporadic CJD (sCJD), 51 patients with vCJD, 46 sCJD controls, and 37 vCJD controls, using Innotest hTau and Innotest P-Thr181, Innogenetics. Results: Concentrations of CSF tau protein were increased in sCJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 10 publications
2
18
0
2
Order By: Relevance
“…Similar results were found with P-tau 231 /T-tau (Buerger, Otto et al 2006). It is important to note that CSF P-tau 181 level in new variant CJD are higher than in sporadic CJD, and this inversely to T-tau CSF level (Goodall, Head et al 2006). So, this ratio P-tau 181 /T-tau is able to differentiate sporadic CJD from new variant with an elevated ratio.…”
supporting
confidence: 73%
“…Similar results were found with P-tau 231 /T-tau (Buerger, Otto et al 2006). It is important to note that CSF P-tau 181 level in new variant CJD are higher than in sporadic CJD, and this inversely to T-tau CSF level (Goodall, Head et al 2006). So, this ratio P-tau 181 /T-tau is able to differentiate sporadic CJD from new variant with an elevated ratio.…”
supporting
confidence: 73%
“…CSF Ab42, t-tau and p-tau-181 were measured by commercially available sandwich ELISA kits (Innotest, Innogenetics, Ghent, Belgium), according to the manufacturer instructions, as previously reported [12,17] CSF S-100b was measured by a commercially ELISA kit (Sangtec 100 ELISA, DiaSorin, Stillwater, MN, USA), according to the manufacturer instructions. All assays were performed sequentially in a clinical routine setting.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…In a clinical setting, putative CSF markers would be most useful in identifying sCJD cases in a cohort of mixed pathologies with a similar presentation of rapidly progressive dementia and therefore suspected to have sCJD. A few studies have addressed this problem [2,12,39] with some limitations, either enrolling a very limited number of patients, or assessing only two or three different CSF markers.…”
Section: Introductionmentioning
confidence: 99%
“…Using a cut-off value of 1300 pg/ml, several studies on the differentiation of CJD from AD and other dementia showed that CSF-tTau level is a highly discriminative marker, which has recently been confirmed in a neuropathological study to be as good as the established 14-3-3 marker for CJD [103]. Elevated values for CSF-tTau have also been found in a bovine variant of CJD [104]. Increases of CSF-tTau levels are observed in several other acute neurological conditions, such as severe malaria [105], Wernicke's encephalopathy [106], pediatric patients with brain tumor, hydrocephalus or serious CNS infections [107].…”
Section: Csf Total Tau: a Biomarker Of Neuronal Degenerationmentioning
confidence: 91%